2016
DOI: 10.3390/su8060570
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Attitudes as WTP Determinants: A Revised Cultural Worldview Scale

Abstract: There has been little attention paid to the systematic measurement issue of general attitudes toward human-culture relationships. This paper applied the Cultural Worldview (CW) scale that was developed by Choi et al. in 2007 (published in the Journal of Cultural Economics), and investigated its dimensionality and relationship with willingness to pay (WTP) for cultural heritage protection through a sequential integration between latent variables and valuation models. A case study of 997 Korean respondents was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Choi et al (2007) developed the cultural worldview scale, which measures individuals' attitudes (i.e., beliefs and perceptions) toward conservation activities at cultural heritage sites. Choi and Fielding (2016) used this scale and found that cultural worldview significantly influences motivation for willingness to pay for preserving cultural heritage sites.…”
Section: Va L U E -Belief-norm (Vbn) Theory and Mgbmentioning
confidence: 99%
“…Choi et al (2007) developed the cultural worldview scale, which measures individuals' attitudes (i.e., beliefs and perceptions) toward conservation activities at cultural heritage sites. Choi and Fielding (2016) used this scale and found that cultural worldview significantly influences motivation for willingness to pay for preserving cultural heritage sites.…”
Section: Va L U E -Belief-norm (Vbn) Theory and Mgbmentioning
confidence: 99%
“…A rich literature has emerged, developing social science-informed valuation methods (e.g., Wilson & Howarth 2002; Van Berkel & Verburg 2014; Kenter et al 2016; Mavrommati et al 2017). Some approaches depart altogether from the economic-dominated perspective towards one that acknowledges diverse worldviews, adopting a wholly different valuation process to capture the interlinkages between nature, people and quality of life (Choi & Fielding 2016; Gould et al 2015; Raymond & Kenter 2016; Pascua et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a standard questionnaire for assessing attitudinal preferences to-wards the built environment in historic Parklands in Nairobi was adopted. This data collection tool shown in appendix I comprised of 32 attitudinal statements designed to better understand how residents perceived their built environment based on the Cultural Worldview (CV) scale, developed by Choi & Fielding (2016).…”
Section: Methodsmentioning
confidence: 99%